Modern industrial statistics : design and control of quality and reliability - Kenett, Ron. S. (Duxbury Press, 1998)
Principles of statistical thinking and analysis: the role of statistical methods in modern industry; Understanding variability in several dimensions; Basic models of probability and distribution functions; Sampling for estimation of finite population quantities... Methods of industrial statistics: Sampling plans for product inspection; Basic tools and principles of statistical process control. Advanced methods of statistical process control...